الوقف المبتكر وأثره في التنمية المستدامة- التعليم أنموذجاً: نماذج تطبيقية من دولة الإمارات العربية المتحدة: INNOVATIVE WAQF AND ITS IMPACT ON SUSTAINABLE DEVELOPMENT - EDUCATION AS A MODEL: APPLIED EXAMPLES FROM THE UNITED ARAB EMIRATES - AlKarim Hammad, Hamza Abed (I-iECONS e-proceedings, 2023)
: هدفت هذه الورقة إلى تحليل ماهية الوقف المبتكر، والتأصيل الشرعي لجواز الابتكار في الوقف، ثم عرض أمثلة على شواهد تطور الأوقاف وابتكاراتها في التاريخ الإسلامي، إضافة إلى الربط بين التعليم والتنمية المستدامة، وانتهاء بعرض نماذج تطبيقية للوقف المبتكر في مجال التعليم وتحليلها في دولة الإمارات الإمارات العربية المتحدة، وقد اتبعت الدراسة المنهج الوصفي، وقد بيّنت الدراسة أن الوقف المبتكر هو: الأفكار الجديدة والأصيلة التي يقصد من تطبيقها تطوير الأوقاف من حيث الأصول التي يتم وقفها، ومصارف تلك الأوقاف، وأن عمدة أدلة جواز الابتكار في الوقف هو القياس؛ إذ إن أي صورة جديدة ومبتكرة من صور الوقف يجرى عليها القياس على الأوقاف الثابتة بالنصوص، فإذا استوفت شروط الوقف، ووجدت فيها العلة الجامعة، دون وجود الموانع والنواقض للقياس؛ صح أن تدرج ضمن صور الوقف المشروعة، وقد انتهت كذلك إلى وجود نماذج تطبيقية للأوقاف المبتكرة في الحضارة الإسلامية؛ مثل: وقف الأعراس، ووقف مواساة المريض، ووقف مؤنس المرضى والغرباء، أما فيما يتعلق بالنماذج التطبيقية للوقف المبتكر في مجال التعليم وتطبيقاته في دولة الإمارات العربية المتحدة؛ فقد انتهت الدراسة إلى وجود نماذج عدة تندرج تحت "الوقف المبتكر" وهو نموذج حديث صممه مركز محمد بن راشد العالمي لاستشارات الوقف والهبة؛ والنماذج هي: وقف: قادة الأعمال الشباب للطلاب، ووقف الاستشارة، ووقف قاعات التدريب، ووقف الاستشارات القانونية، ووقف المعرفة، ووقف الثقافة. This paper aims to analyze the nature of innovative waqf, its legal foundation, and present examples of the evolution and innovations within the history of Islamic endowments. Additionally, it links education and sustainable development, concluding with applied models of innovative waqf in education and their analysis in the United Arab Emirates. The study employs a descriptive methodology and demonstrates that innovative waqf encompasses novel and authentic ideas intended for developing endowments in terms of their assets and expenditures. The primary criterion for the permissibility of innovation in waqf is measurement. Any new and innovative form of waqf is assessed against established textual endowments. If it meets the waqf conditions and serves a universal purpose without any impediments, it is considered a legitimate form of waqf. The study also highlights practical examples of innovative waqf in Islamic civilization, such as the endowment for weddings, patient care, and consoling the sick and strangers. Regarding applied models of innovative waqf in education and their applications in the United Arab Emirates, the study identifies several models falling under the category of "Innovative Waqf." A recent model, designed by the Mohammed Bin Rashid Global Centre for Waqf and Endowment Consultancy, includes: Youth Business Leaders for Students Waqf, Consultation Waqf, Training Hall Waqf, Legal Consultation Waqf, Knowledge Waqf, and Cultural Waqf.